IMPELEMETASI MEDIA APE DALAM MENINGKATKAN MOTIVASI BELAJAR PAI ANAK DI TK IT ANAK SOLEH PERAYA, LOMBOK TENGAH - Muhibbin, Muhibbin; Harjanty, Rokyal (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to explore the types of APE used by teachers in fostering children's PAI learning motivation, teacher preparation in implementing educational game tools to foster children's PAI learning motivation and finding out the obstacles faced by teachers in children's PAI learning at ANAK SOLEH IT Kindergarten. Type of qualitative research. The instruments used in this research were the researchers themselves and notebooks. Data collection techniques use observation, interviews and documentation. The results of this research show the obstacles faced in implementing APE in children's PAI learning, such as the different concentrations of children, there are only 5 types of APE relating to children's PAI learners, APE is not sufficient, the majority of children like other types of games according to they are more interesting. And lack of order in APE management. There are five types of APE media used by teachers in children's PAI learning activities, namely hijaiyah letter puzzles, ablution movement puzzles, prayer movement puzzles, Muslim places of worship puzzles and prayer time displays. And the APE implementation process includes: appropriate APE, attracting motivation to practice how to play.